Accessibility perception of chilean para-athletes, road to Santiago 2023 - Nicolás Contreras Jofré; José Pinochet Gilli; Enrique Aguayo Carrasco; Matías Binimelis Hermosilla; Sebastián Perez Nuñez; Rodrigo Vergara Ortuzar; Fernando Ignacio Muñoz Hinrichsen (Universidad de Costa Rica, 2022)
The objective of this research is three-fold: 1) to understand Para-athletes' perceptions on accessibility regarding Santiago 2023 ParapanAmerican games' future venues, 2) to establish differences in perception due to the origin of the disability, and 3) document alignment, if any, with athletes with high support needs (AHSN).This research is a two-phased quantitative cross-sectional study, which at the first stage developed the "Para-athletes Perception on Accessibility Survey" (PPA-D) and, at the secondstage, the survey was applied to 96 Chilean Para-athletes (77.8% men, mean age = 31.0 ±11.6 years old). The test obtained a validation coefficient of = 0.96. Regarding the sample characteristics, 16.6% corresponded to participants with visual impairment, 35.1% were AHSN, 51.5% were linked to high-level competition, and 59.3% travelled on their own to their training sessions. A negative perception of accessibility was found, mainly concerning minibuses, elevators, and restroom spaces, affecting mostly AHSNwith visual impairment (F1.101 = 14.01, p = .0003).We conclude that it is important to address gender, disability, and AHSN gaps to guarantee equitable participation under a framework of the law and social rights.